(untitled) - ANWAR, QOIRUL (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
In the information age people live with ease in obtaining the information. Newspapers become an alternative source of information. Recognizing the need for information into business opportunities for companies to compete in it, so that the emerging of various types of newspaper. Competition requires companies to prepare a marketing strategy for the product to be accepted by consumers. In order for the company ahead of the competition requires careful planning of the marketing activities, such as a product to be marketed, the price that attractive and affordable by the target customers and how the companies promote their products to customers. This research is a quantitative survey approach that seeks to determine the effect of marketing strategies in the form of sales promotion programs on consumers purchasing behavior in KOMPAS. Data retrieval techniques with Non-Probability Sampling with Quota Sampling. This study uses a simple linear regression with a sample of 160 respondents. The results of this research showed that the effect of sales promotion programs (X) consisting of indicator: The number of incentives (X1.1), Media Promotion (X1.2), Old Promotion (X1.3), by a relatively very small daily KOMPAS is equal to 0,6% and the balance of 99,4% is explained by other variables outside of the study Keywords: Sales Promotion, Consumers Purchasing Behaviour